The role of Bhabinkamtibmas through Sambang to prevent theft of two-wheeled motorized vehicles - Orchida Pertiwi Agung Putri (Tanggon Kosala, 2021)
The background of this research comes from the high level of motorcycle auto theft that’s been happening in the jurisdiction of Polsek Purwakarta Kota. Indonesian National Police have done preemptive and preventive efforts and one of them is sambang (personal approach to people) in order to prevent motorcycle auto theft. Because of that, the purpose of this research is to discover the role of bhabinkamtibmas through sambang (personal approach to people) in order to prevent motorcycle auto theft and the factors that effect Bhabinkamtibmas through sambang to prevent motorcycle auto theft. This research uses “the element of communication” theory and “the element of management” theory. Whereas for the concepts consist of role concept, sambang concept, prevention concept, and auto theft concept. This research used qualitative approach whilst the type of research is descriptive research. Data is collected by doing interviews, observation, and document studies. The result of this research gives conclusion that the role of Bhabinkamtibmas through sambang by appealing the society everyday by informing message to maintain alertness and be careful. In practicing sambang Bhabinkamtibmas refers to Perkap Nomor 3 Tahun 2015 about Community Policing. Meanwhile factors that effect it consist of man, money, method, material, market and machine whereas there’s support factors and inhibit factors. The suggestion from this research to enhance the role of sambang Bhabinkamtibmas (1) upgrade the qualification of Bhabinkamtibmas (2) giving reward to Bhabinkamtibmas that have outstanding achievements (3) The use of media in order for the society to comprehend the sambang (4) Making communication network in WhatsApp (5) Not involving Bhabinkamtibmas in other police functions (6) To even the equipment and infrastructure for Bhabinkamtibmas.